Development of Criminal Procedure Legislation on Forensic Science, Experts and Specialists - Vadim N. Makhov (Теория и практика судебной экспертизы)
Key stages in the establishment and further development of the institution of special knowledge in Russia is analyzed, from the pre-revolutionary period to our days. The procedural status of forensic science, forensic experts and forensic specialists in the Russian criminal procedure is examined. The procedural status of experts and specialists in the Russian criminal procedure is compared to that in other countries. The author observes that in the early stages the functions of knowledgeable persons were not clearly delineated by the law, and there were no regulations on how forensic evidence analysis should be requested and conducted, but by the mid-1920s the terms «forensic science» and «forensic expert» were present in the Russian legislation. The procedure for requesting and conducting forensic examinations was defined starting in 1960; the use of special knowledge in investigative actions became the function of the specialist. The status of the specialist was further elaborated in 1966. With the adoption of the Criminal Procedure Code of the Russian Federation in 2001, the specialist's legal status was expanded, giving them the right to present their opinion and testify on the probative value of evidence, and their rights and responsibilities were refined.